1999
DOI: 10.1159/000008623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hexose Sugars: Glucose, Fructose, Galactose and Mannose on Wound Healing in the Rat

Abstract: The effects of four hexose sugars (D-glucose, D-fructose, D-galactose, D-mannose) on the developing granulation tissue in rats were examined. Cylindrical hollow sponge implants were used as an inductive matrix for the growth of granulation tissue. In the test group, the implants were injected with 0.1 ml of solution containing the different hexoses in 0.01, 0.1 and 1 M concentrations daily for 7 days while the implants of the control groups were injected with 0.1 ml of phosphate-buffered saline solution only. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 26 publications
4
16
0
1
Order By: Relevance
“…Similarly, the reports of perceived improvement in the experience of arthritic pain lend support to the findings of saccharide involvement in arthritic conditions (A. Alavi & Axford, 2008;Gelderman, et al, 1998;Kossi, Peltonen, Ekfors, Niinikoski, & Laato, 1999;Lefkowitz, et al, 1999). In addition, the perceived changes in psychological well-being are consistent with the role of polysaccharides within the brain that may influence the regulation of mood, namely cell interactions and neurotransmitter response (Chicoine & Bahr, 2007;Hirano, et al, 2003;Kleene & Schachner, 2004;Krishnan & Nestler, 2010;Martin, 2002;Matthies, et al, 1996).…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, the reports of perceived improvement in the experience of arthritic pain lend support to the findings of saccharide involvement in arthritic conditions (A. Alavi & Axford, 2008;Gelderman, et al, 1998;Kossi, Peltonen, Ekfors, Niinikoski, & Laato, 1999;Lefkowitz, et al, 1999). In addition, the perceived changes in psychological well-being are consistent with the role of polysaccharides within the brain that may influence the regulation of mood, namely cell interactions and neurotransmitter response (Chicoine & Bahr, 2007;Hirano, et al, 2003;Kleene & Schachner, 2004;Krishnan & Nestler, 2010;Martin, 2002;Matthies, et al, 1996).…”
Section: Discussionsupporting
confidence: 65%
“…pretreatment with D-mannose, also characterized to exert anti-inflammatory effects [76,77], significantly altered the efficacy of a subsequent i.t. pDNA-IL-10 injection in that complete and enduring suppression of bilateral allodynia was observed at pDNA-IL-10 doses five-fold lower than previously documented (Figure 2) [24,46].…”
Section: Discussionmentioning
confidence: 99%
“…D-mannose is a simple hexose sugar with a molecular weight of 180.2 and is known to: decrease inflammatory processes during wound healing [76], reduce oxidative bursts required during inflammation [106], suppress adjuvant-induced arthritis in a rat model [107], inhibit LPS-induced IL-1β, TNF-α decrease NF-kB/p65 critical for proinflammatory cytokine expression, and decrease leukocyte influx following intratracheal instillation of LPS, which is a model of sepsis-associated acute lung injury and respiratory distress syndrome [77,108]. …”
Section: Discussionmentioning
confidence: 99%
“…It was of note that in the present study, mannose dose-dependently inhibited LPS-induced neutrophil infi ltration, which was identifi ed by decreased leukocytes, especially PMNs, in the BALF and amelioration of lung pathology. Previous studies have shown that mannose causes a marked decrease in the number of total leukocytes and neutrophils in wound fl uid and decreases tissue granulation formation in an experimental wound model [4]. Its derivative, mannose-6-phosphate, showed effects similar to mannose.…”
Section: Discussionmentioning
confidence: 86%
“…Mannose is a simple hexose sugar with a molecular weight of 180.2, and it has been found to have anti-infl ammatory effects. Mannose treatment inhibits the infl ammatory reaction in wound healing and decreases leukocytes, especially neutrophils, in wound fl uid [4]. Mannose also inhibits the neutrophil oxidative burst, which plays an important role in infl ammation [5].…”
Section: Introductionmentioning
confidence: 99%